Benzodiazepines Associated With Acute Respiratory Failure in Patients With Obstructive Sleep Apnea - Wang, Sheng-Huei; Chen, Wei-Shan; Tang, Shih-En; Lin, Hung-Che; Peng, Chung-Kan; Chu, Hsuan-Te; Kao, Chia-Hung (Frontiers in Pharmacology, 2019)
AIMS: Obstructive sleep apnea (OSA) and insomnia commonly coexist; hypnotics are broadly prescribed for insomnia therapy. However, the safety of hypnotics use in OSA patients is unclear. We conducted a retrospective case-control study to investigate the risk of adverse respiratory events in hypnotics-using OSA patients. METHODS: We obtained data from the Taiwan National Health Insurance Database from 1996 to 2013. The case group included 216 OSA patients with newly-diagnosed adverse respiratory events, including pneumonia and acute respiratory failure. The control group included OSA patients without adverse respiratory events, which was randomly frequency-matched to the case group at a 1:1 ratio according to age, gender, and index year. Hypnotics exposure included benzodiazepines (BZD) and nonbenzodiazepines (non-BZD). A recent user was defined as a patient who had taken hypnotics for 1 to 30 days, while a long-term user was one who had taken hypnotics for 31 to 365 days. RESULTS: Multivariable adjusted analysis showed recent BZD use is an independent risk for adverse respiratory events (OR = 2.70; 95% CI = 1.15–6.33; P < 0.001). Subgroup analysis showed both recent and long-term BZD use increased the risk of acute respiratory failure compared to never BZD use (OR = 28.6; 95% CI = 5.24–156; P < 0.001, OR = 10.1; 95% CI = 1.51–67.7; P < 0.05, respectively). Neither BZD nor non-BZD use increased the risk of pneumonia in OSA patients. CONCLUSION: BZD use might increase the risk of acute respiratory failure in OSA patients.